Systematic analysis of the UDP-glucosyltransferase family: discovery of a member involved in rutin biosynthesis in Solanum melongena - Gan, Yuwei; Yu, Bingwei; Liu, Renjian; Shu, Bingbing; Liang, Yonggui; Zhao, Yafei; Qiu, Zhengkun; Yan, Shuangshuang; Cao, Bihao (Frontiers in Plant Science, 2023)
Eggplant (Solanum melongena) is an economically important crop and rich in various nutrients, among which rutin that has positive effects on human health is found in eggplant. Glycosylation mediated by UDP-glycosyltransferases (UGTs) is a key step in rutin biosynthesis. However, the UGT gene has not been reported in eggplant to date. Herein, 195 putative UGT genes were identified in eggplant by genome-wide analysis, and they were divided into 17 subgroups (Group A-P and Group R) according to the phylogenetic evolutionary tree. The members of Groups A, B, D, E and L were related to flavonol biosynthesis, and rutin was the typical flavonol. The expression profile showed that the transcriptional levels of SmUGT genes in Clusters 7-10 were closely related to those of rutin biosynthetic pathway genes. Notably, SmUGT89B2 was classified into Cluster 7 and Group B; its expression was consistent with rutin accumulation in different tissues and different leaf stages of eggplant. SmUGT89B2 was located in the nucleus and cell membrane. Virus-induced gene silencing (VIGS) and transient overexpression assays showed that SmUGT89B2 can promote rutin accumulation in eggplant. These findings provide new insights into the UGT genes in eggplant, indicating that SmUGT89B2 is likely to encode the final enzyme in rutin biosynthesis.